Crisis Discourse Analysis in Japanese Language Education: A Study of Media Representation and Student Response - Launingtia, I Gusti Ayu Niken; I Nengah Suandi; I Nyoman Sudiana; I Putu Mas Dewantara (Global Action and Education for Society, 2025)
This article examines the application of crisis discourse analysis in Japanese language learning by analyzing how Japanese media represent crises and how students respond to them. The crises include natural disasters, pandemics, and social issues as reflected in authentic media texts such as news articles and advertisements. This study employs a descriptive-qualitative approach grounded in discourse analysis theories by Fairclough and Van Dijk. Findings indicate that integrating crisis discourse into language learning enhances students’ critical literacy and their awareness of the social construction of meaning in the Japanese language.